Duma [videorecording (DVD)] - Ballard, Carroll; Michaletos, Alexander; Walker, Eamonn; Scott, Campbell; Davis, Hope, 1967-; Hopcraft, Xan; Hopcraft, Carol Cawthra (Warner Home Video, 2005)
The powerful tale of an unbreakable bond of friendship between a cheetah named Duma and a courageous young boy named Xan. Xan faces the true test of love when he must cross the wilds of Southern Africa to return his best friend to his rightful home.